Effect of welding processes on the residual stress and distortion in type 316LN stainless steel weld joints. (August 2015) - Vasantharaja, P.; Vasudevan, M.; Palanichamy, P.
Abstract: The effect of welding processes on the microstructure, residual stresses and distortion in 16 mm thick 316LN stainless steel weld joints made by TIG and A-TIG (activated flux tungsten inert gas) welding processes involving different joint configurations have been studied. The joint configurations employed were double V-groove edge preparation for double side TIG welding, square-butt preparation for double side ATIG welding and Y groove preparation for weld joint made by both TIG and ATIG welding processes. All the weld joints passed radiographic examination. Microstructural characterization was carried out using optical microscope. Residual stresses were determined using ultrasonic technique employing LCR waves, and distortion measurements were carried out using height gauge. The three weld joints exhibited different microstructures, peak tensile residual stress values and distortion. The weld joint fabricated by double side A-TIG welding exhibited the lowest peak tensile residual stress value and also minimum distortion.